Philosophy for Children: Some Assumptions and Implications - Lipman, Matthew (ETHICS IN PROGRESS, 2011)
It is a pleasure to be able to thank the editors of Ethik und Sozialwissenschaften for inviting me to write this paper about the Philosophy for Children program, with which I have been associated since it began at the end of the 1960's